Consideraciones sobre las pruebas regionales de yuca en Colombia y sus alternativas - Rodríguez, N. (International Center for Tropical Agriculture, 1991)
The characteristics of cassava regional trials are presented and their role and the limitations to their use in Colombia are discussed. In the scheme presented, emphasis is placed on the relationships between research and technology transfer; the latter constitutes the basic link between research and agricultural production. Two projects carried out with this methodology are mentioned, namely (1) a collaborative project between CIAT and the Instituto Colombiano Agropecuario on Colombia's North Coast, in which cassava genotypes are assessed, and (2) a project carried out in the dept. of Cauca in which farmers evaluate cassava, bean, and maize genotypes. (CIAT)